Transferrin Saturation Inversely Correlates with Platelet Function - Barale, Cristina; Senkeev, Rouslan; Napoli, Franca; De Gobbi, Marco; Guerrasio, Angelo; Morotti, Alessandro; Russo, Isabella (Thrombosis and Haemostasis, 2019)
Background The association between iron overload (IO) and risk of cardiovascular disease is controversial. Epidemiological studies have found a significant negative association of transferrin (Tf) saturation and cardiovascular events suggesting that higher body iron possibly confer a protective effect towards developing cardiovascular events. The biological mechanisms of this phenomenon are unknown.Objective This article investigates the role of IO on platelet reactivity.Materials and Methods This study was a prospective case–control study comparing 45 patients with IO, mostly characterized by the HFE gene mutations C282Y and/or H63D, with 32 healthy controls. We evaluated: (1) platelet aggregation in both platelet-rich plasma and whole blood, (2) platelet membrane expression of the activation marker CD62P, (3) activation of platelet signalling phosphoinositide 3-kinase /Akt and mitogen-activated protein kinase/extracellular signal-regulated kinases (Erk)-1/2 pathways, (4) a pattern of in vivo platelet activation markers, and (5) iron biomarker predictors of platelet reactivity.Results IO patients had significantly lower platelet aggregability, expression of CD62P and phosphorylation amounts of pAkt and pErk-2 in response to agonists. Furthermore, patients with higher Tf saturation levels were characterized by lower circulating levels of sCD40L, PDGF-BB and thromboxane B2. Platelet aggregation and activation parameters inversely correlated with Tf saturation and the stepwise multivariate regression analysis underlined the role of Tf saturation in predicting platelet reactivity. We also found that in vitro platelet exposure to diferric Tf, but not to iron-depleted TF, dose-dependently inhibited platelet function in all investigated subjects.Conclusion Tf saturation is inversely associated with platelet reactivity and this could explain, at least in part, the association of high Tf and lower risk of cardiovascular diseases in IO.
Keywords: platelets; transferrin; iron; haemochromatosis